Expanding the Nudge: Designing Choice Contexts and Choice Contents - Grill, Kalle; Justus Liebig University Giessen (My University, 2014)
To nudge is to design choice contexts in order to improve choice outcomes. Richard Thaler and Cass Sunstein emphatically endorse nudging but reject more restrictive means. In contrast, I argue that the behavioral psychology that motivates nudging also motivates what may be called jolting--i.e. the design of choice content. I defend nudging and jolting by distinguishing them from the sometimes oppressive means with which they can be implemented, by responding to some common arguments against nudging, and by showing how respect for preferences over option sets and their aggregate properties may require the trimming of option sets, as well as helpful choice contexts.
Keywords: Choice Design; Default-setting; Incentives; Nudging; Respect for Preferences; ddc:100; ddc:330